UNITY OF THEORY AND PRACTICE AS A FACTOR OF THE EDUCATION OF MORAL-ETHICAL VALUES IN EUROPEAN PEDAGOGICAL CONCEPTS OF THE INDUSTRY INSTITUTIONAL - Olga Tsybulko ("Scientific Information Agency "Science-technologies-information" LLC, 2019)
The article deals with the issues of unity of theory and practice as a factor of education of moral and ethical values in European pedagogical concepts of the period of industrial society formation. Particular attention is paid to the fundamental concepts of education of moral values in pedagogy. Possibilities of using world pedagogical thought by Ukrainian teachers are revealed in the article.